In vitro activity of essential oils against adult and immature stages of Ctenocephalides felis felis. Issue 3 (6th March 2020) - dos Santos, João Vitor Barbosa; de Almeida Chaves, Douglas Siqueira; de Souza, Marco André Alves; Riger, Cristiano Jorge; Lambert, Monique Moraes; Campos, Diefrey Ribeiro; Moreira, Leandra Oliveira; dos Santos Siqueira, Rosiane Conceição; de Paulo Osorio, Rodrigo; Boylan, Fabio; Correia, Thaís Ribeiro; Coumendouros, Katherina; et al.
Abstract: Essential oils (EOs) are considered a new class of ecological products aimed at the control of insects for industrial and domestic use; however, there still is a lack of studies involving the control of fleas. Ctenocephalides felis felis, the most observed parasite in dogs and cats, is associated with several diseases. The aim of this study was to evaluate the in vitro activity, the establishment of LC50 and toxicity of EOs from Alpinia zerumbet (Pers.) B. L. Burtt & R. M. Sm, Cinnamomum spp., Laurus nobilis L., Mentha spicata L., Ocimum gratissimum L. and Cymbopogon nardus (L.) Rendle against immature stages and adults of C. felis felis . Bioassay results suggest that the method of evaluation was able to perform a pre-screening of the activity of several EOs, including the discriminatory evaluation of flea stages by their LC50 . Ocimum gratissimum EO was the most effective in the in vitro assays against all flea stages, presenting adulticide (LC50 = 5.85 μ g cm − 2 ), ovicidal (LC50 = 1.79 μ g cm − 2 ) and larvicidal (LC50 = 1.21 μ g cm − 2 ) mortality at low doses. It also presented an excellent profile in a toxicological eukaryotic model. These findings may support studies involving the development of non-toxic products for the control of fleas in dogs and cats.